Instagram as an innovative tool for professional training in library, information, and archival studies at higher technical education institutions - Shlenova, Maryna (Professional Art Education, 2025)
This article considers Instagram as an innovative tool for developing educational resources aimed at training future specialists in library, information, and archival studies at higher technical education institutions in the context of educational digitalization. Leveraging its functional features, such as Stories, Reels, infographics, and interactive polls, Instagram facilitates the creation of visually oriented, interactive content that fosters professional competencies, including visual literacy, media communication, critical thinking, and creativity. The platform aligns with principles of integrated, competency-based, and student-centered learning, adapting the educational process to the digital preferences of Generation Z, for whom social media is integral to daily life. The study analyzes the integration of Instagram into professional training, evaluates its impact on student motivation, digital literacy, and creativity, and provides recommendations for establishing specialized educational accounts as virtual learning environments. Particular emphasis is placed on ethical and psychosocial considerations, including digital addiction, data privacy, and the need for methodological training to ensure educators’ effective use of Instagram. By supporting asynchronous learning, removing temporal and spatial barriers, and enabling gamified approaches (e.g., quizzes and quests) and digital portfolio development, Instagram is especially relevant for distance and blended learning formats. The article underscores Instagram’s pedagogical value, proposing innovative learning approaches that align with the demands of the digital economy and contemporary labor market. Future research directions include developing didactic models for Instagram content tailored to library, information, and archival studies, analyzing its impact on students’ professional identity and academic mobility, evaluating its effectiveness across diverse higher education institutions, and formulating methodological guidelines for educators to create ethical and secure digital learning environments